2000
DOI: 10.21273/hortsci.35.6.1107
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Delays Senescence in Cut Gladiolus Spikes

Abstract: Florets of cut gladiolus (Gladiolus ×grandiflora hort. cv. Fujinoyuki) spikes kept at 25 °C under 14 h light/10 h dark condition showed severe wilting 4 days after flower opening. Treatment with 0.1 m trehalose prolonged vase-life 2 days, whereas inhibitors and other sugars had no effect. The upper florets also opened properly in trehalose-treated spikes, but not in cycloheximide-treated ones. After 4 days, the first florets of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
5
17
0
Order By: Relevance
“…S1). These results were consistent with the suggestion that trehalose may play a role in promoting water retention in cut flowers (Otsubo and Iwaya-Inoue, 2000).…”
Section: Effects Of Trehalose and Validamycin A On Quality Of Infloresupporting
confidence: 92%
See 2 more Smart Citations
“…S1). These results were consistent with the suggestion that trehalose may play a role in promoting water retention in cut flowers (Otsubo and Iwaya-Inoue, 2000).…”
Section: Effects Of Trehalose and Validamycin A On Quality Of Infloresupporting
confidence: 92%
“…Trehalose treatment also suppressed water loss ( Fig. S1) and enhanced viability in petals, although slight wilting of the bracts of cut gladiolus has been observed (Otsubo and Iwaya-Inoue, 2000). Yamada et al (2003) reported that trehalose has a suppressive effect on apoptotic cell death.…”
Section: Roles Of Sucrose and Trehalosementioning
confidence: 88%
See 1 more Smart Citation
“…5). TNBT staining reflects tissue viability by showing the quantity of active dehydrogenase in existence through observing purplish-black formazan as a result of reduced tetrazolium salts (Rosa and Tsou , 1961;Otsubo and Iwaya-Inoue, 2000). The petal tissues treated by TNBT were well stained in the orchid plants before ethylene exposure, particularly the parenchyma cells adjacent to the vascular bundles (Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Anserwadekar and Patil (1986) observed that 6 % sucrose was a good solution for prolonging the vase life of Gladiolus spikes, whereas Mayak et al (1973) and Bravdo et al (1974) found that higher sugar concentrations (up to 50 %) improve the opening and size of the florets and increase flower spike longevity, the amount of solution absorbed decreasing with increasing solution concentration. Treatment with 0.1 M trehalose, a disaccharide consisting of 2 linked glucose units, has been found to prolong vase life and improve spike quality whereas inhibitors and other sugars had no effect (Otsubo & Iwaya-Inoue, 2000;Yamane et al, 2005).…”
Section: Handling Of the Spikesmentioning
confidence: 99%